The effectiveness of promotion mix towards TM (consumer products) / Waheddah Sahimin (Faculty of Business and Management, 2007)
The marketing concept is the philosophy that firms should analyze the needs of the customers and then makes decisions to satisfy those needs, better than competition. Today most firms have adopted the marketing concept, but this has this not has been the case. In 1776, in The Wealth of Nations, Adam Smith wrote that the need of the producers should be considered only with regards to meeting the need of the customers. While this philosophy is consistent with the marketing concept, it would not be adopted widely until nearly 200 years late.To better understand the marketing concept, it is worthwhile to put in perspective by reviewing other philosophies that was should be predominant. While these alternative concepts prevailed during different historical time frames.